Dystocia due to Schistosomus Reflexus Foetal Monstrosity in a Jaffarabadi Buffalo: A Case Report - N Borakhatariya, Devasee; N Kethavath, Giri; R Nandaniya, Nirbhay; J Savaliya, Krinal; B Gadhadara, Ashish; M Sanghani, Yash (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Among buffalo breeds, Jaffarabadi is the heaviest and most commonly suffers from dystocia for a variety  of reasons, including uterine torsion, incomplete cervical  dilatation, an oversized foetus, dropsical conditions of  the foetus and foetal membranes, and congenital foetal  monstrosities such as schistosomus reflexus. Several authors  reported the prevalence of the schistosomus reflexus foetal  monster in many species, i.e., cattle, buffalo, sheep, goat, dog,  and equine (Kumar et al., 2019a,b; Duarte et al., 2022; Deepak  et al., 2023; Harika et al., 2023; Yadav et al., 2024). The presence  of a deformed spine and exposed abdominal and thoracic  viscera allows for the gross identification of schistosomus  reflexus. Anomalies of the ovum, embryo, or foetus that result  in skeletal developmental abnormalities are typically cited  as the etiology for the emergence of foetal monstrosities,  however, definite etiology is still ambiguous (Munif et al., 2023). The majority of affected foetuses are not viable.  Congenital defects are seen as economically significant  since they hinder spontaneous foetal delivery. Dystocia is  inevitable in the cases of the foetal monstrosities amongst  farm animals (Borakhatariya et al., 2017; Borakhatariya et al., 2020). In such instances, cases can be managed by Caesarean  section when there is insufficient space in the birth canal to  apply manual obstetrical mutations, or by partial or complete  foetotomy for per-vaginum delivery. Such cases need to be  treated promptly because if they are not, the dead foetus  may develop emphysema, which could lead to toxaemia and  the collapse of the dam. An unusual case of dystocia due to  schistosomus reflexus foetal monster clinically managed  with Caesarean section in a Jaffarabadi buffalo is described  in this case report.
Keywords: buffalo; breeds; Jaffarabadi; heaviest; variety